Initial in vitro evaluations of antibacterial activities of glucosinolate enzymatic hydrolysis products against plant pathogenic bacteria - Aires, A. (2015)
Aims: The aim of the study was to evaluate the in vitro antibacterial effects of glucosinolate hydrolysis products (GHP) against plant pathogenic micro-organisms namely Agrobacterium tumefaciens, Erwinia chrysanthemi, Pseudomonas cichorii, Pseudomonas tomato, Xanthomonas campestris and Xanthomonas juglandis. Methods and Results: Using a disc diffusion assay, seven different doses of 10 GHP were tested against each bacteria. The results showed that the isothiocyanates were potent antibacterials, whilst the other GHP were much less efficient. Moreover, the antibacterial effects were dose-dependent, increasing with the dose applied; 2-phenylethylisothiocyanate and sulforaphane showed the strongest inhibitory effects. The overall results show a great potential for using the isothiocyanates as an alternative tool to control undesired bacterial growth in plants. Conclusions: Glucosinolate hydrolysis products and more specifically the isothiocyanates: benzylisothiocyanate, 2-phenylethylisothiocyanate, the isothiocyanate Mix and sulforaphane, were effective phytochemicals against the in vitro growth of the phytopathogenic bacteria. The antibacterial activity exhibited by these phytochemicals reinforces their potential as alternatives to the traditional chemical control of phytopathogenic bacteria. Significance and Impact of the Study: This current in vitro study is the first providing comparative data on GHP as potential control agents for plant pathogenic bacteria. However, more studies are needed to determine their possible allelopathic impacts e.g. inhibition of plant growth and negative effects on beneficial soil bacteria and fungi (mycorrhizae)